Prevalence and Main Outcomes of Placenta Accreta Spectrum: A Systematic Review and Meta-analysis. Issue 2 (June 2020) - Jauniaux, E.; Bunce, C.; Grønbeck, L.; Langhoff-Roos, J.
Abstract : ( Am J Obstet Gynecol . 2019;221:208–218) Placenta accreta spectrum occurs when the villous tissue of the placenta adheres or invades the uterine wall, at times even connecting surrounding pelvic organs and vasculature. During delivery, these adherent villi result in either parts or the entire placenta failing to detach spontaneously from the uterine wall. Access to specialist centers, blood banks, and neonatal and maternal intensive care is inconsistent in some high-income countries and often restricted or nonexistent in most low- and middle-income countries. This study was a systematic review and meta-analysis evaluating the prevalence of placenta accreta spectrum in studies of the general population. Specifically the authors evaluated the heterogeneity across studies in clinical diagnostic criteria reporting to assess the impact on incidence of maternal outcomes.